Teachers’ Strategies For Addressing Challenges In Digital-Era Pancasila Education: A Qualitative Study Of Fifth-Grade Elementary Students - Hasriana Hasriana; Chairan Zibar L. Parisu; Erwin Eka Saputra (CV. Gerasi Insan Nusantara, 2025)
This study aimed to investigate the challenges encountered by teachers in implementing Pancasila Education in the digital era, examine the strategies employed to address these challenges, and analyze the contribution of these strategies to students' engagement and understanding of Pancasila values. This study employed a qualitative approach with a case study design. The primary informant was a fifth-grade teacher at a public elementary school. Data were collected through structured interviews, participant observation, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, while data credibility was established through methodological, source, and time triangulation. The findings revealed that the major challenges in teaching Pancasila Education in the digital era included students' distraction from digital devices, exposure to digital content that was inconsistent with Pancasila values, limited digital literacy, and difficulties in consistently internalizing Pancasila values in students' daily lives. To address these challenges, the teacher implemented interactive digital learning media, active and collaborative learning strategies, direct supervision of digital device use, and the cultivation of Pancasila values through role modeling and habituation. These strategies contributed to increased student interest, classroom engagement, and understanding of Pancasila values, while also supporting the development of discipline, responsibility, cooperation, and respect for others. The study concludes that the integration of digital technology with character-oriented education can serve as an effective approach to addressing the challenges of Pancasila Education in the digital era. However, the use of technology should remain balanced with teacher guidance, exemplary behavior, habituation, and continuous character development.